Breaking Barriers: Empowering Visual Impaired Students with Audio-Assisted Balinese Script Relief Media for Enhanced Literacy at A Special Public School - Sudarma, I Komang; Sujana, I Wayan; Dewantara, Kadek Andre Karisma; Ardiyasa, I Nyoman Suka; Sudiartini, Ni Pande Kadek Dewi (Universitas Negeri Makassar, 2024)
The difficulties faced by teachers at a Special Public School in teaching Balinese script literacy to visually impaired children have resulted in low literacy skills in Balinese script among these students. In order to maximize Balinese script learning, appropriate learning media tailored to the characteristics of visually impaired children are necessary. This study aims to determine the design, feasibility, and effectiveness of the Relief Balinese Script Media (Reaksi) assisted by audio to improve the Balinese script literacy of visually impaired students at a Special Public School. The study utilizes the ADDIE development model with a quantitative research design. Data collection methods include written tests assessing Balinese script writing. The subjects of this study are 12 visually impaired students. The results of this development study are as follows: (1) the design of the audio media achieved a score of 93.15%, qualifying as excellent; (2) the Reaksi media was deemed feasible, scoring 91.44% and qualifying as excellent; (3) the obtained t-value was 77.97, while the t-table value at a significance level of 5% was 2.101. These results indicate that the t-value is greater than the t-table value, thus rejecting H0 and accepting H1. Therefore, it can be concluded that the Relief Balinese Script Media (Reaksi) assisted by audio is effectively applied to improve the Balinese script literacy of visually impaired students at a Special Public School. This audio-assisted Relief Balinese Script Media (Reaksi) helps visually impaired students recognize the actual forms of Balinese script, thereby enhancing the literacy skills of Balinese script reading and writing among visually impaired students.